Implementasi Building Information Modelling (BIM) 5D pada Pekerjaan Kost 2 Lantai Tipe 600 - Rajagukguk, Fanji Fauzi; Hendriyani, Irna; Pratiwi, Reno (Universitas Ibn Khaldun, 2025)
Technological advances in the world of construction have brought many benefits, especially in building pomodeling, scheduling, cost estimation, volume changes, building continuity, and building management. A widely used technology is Building Information Modeling (BIM). Accurately estimating construction costs is essential to obtain efficient values during planning. In calculating the cost of construction projects, conventional methods are still often used, resulting in increased costs. Therefore, this research will use the concept of Building Information Modeling (BIM) 5D which aims to analyze the volume and cost estimates, as well as analyze the difference in volume and cost between the BIM method and the Consultant's calculations on the structural work of the construction of the 2-storey boarding house Sepinggan Baru 1. The results showed that the structural work of the construction of the 2-storey boarding house Sepinggan Baru 1 with the Bim 5D concept had a volume of ironwork of 23305.48 kg at a cost of Rp 421.992.326,4, and a concrete volume of 109.05 at a cost of Rp 215,386,847.00. The difference in iron volume is 17,3% while the difference in concrete volume is 0.84%. This means that the calculation using the 5D Building Information Modeling (BIM) concept with the help of Autodesk Revit Software is lower than the cost planning produced by the consultant.